A Novel SPG7 Gene Pathogenic Variant in a Cypriot Family With Autosomal Recessive Spastic Ataxia - Votsi, Christina; Ververis, Antonis; Nicolaou, Paschalis; Christou, Yiolanda-Panayiota; Christodoulou, Kyproula; Zamba-Papanicolaou, Eleni (Frontiers in Genetics, 2022)
The SPG7 gene encodes the paraplegin protein, an inner mitochondrial membrane - localized protease. It was initially linked to pure and complicated hereditary spastic paraplegia with cerebellar atrophy, and now represents a frequent cause of undiagnosed cerebellar ataxia and spastic ataxia. We hereby report the molecular characterization and the clinical features of a large Cypriot family with five affected individuals presenting with spastic ataxia in an autosomal recessive transmission mode, due to a novel SPG7 homozygous missense variant. Detailed clinical histories of the patients were obtained, followed by neurological and neurophysiological examinations. Whole exome sequencing (WES) of the proband, in silico gene panel analysis, variant filtering and family segregation analysis of the candidate variants with Sanger sequencing, were performed. RNA and protein expression as well as in vitro protein localization studies and mitochondria morphology evaluation were carried out towards functional characterization of the identified variant. The patients presented with typical spastic ataxia features while some intrafamilial phenotypic variation was noted. WES analysis revealed a novel homozygous missense variant in the SPG7 gene (c.1763C>T, p.Thr588Met), characterized as pathogenic by more than 20 in silico prediction tools. Functional studies showed that the variant does not affect neither the RNA or protein expression, nor the protein localization. However, aberrant mitochondrial morphology has been observed thus indicating mitochondrial dysfunction and further demonstrating the pathogenicity of the identified variant. Our study is the first report of an SPG7 pathogenic variant in the Cypriot population and broadens the spectrum of SPG7 pathogenic variants.